Abnormal EEG Effects of Acute Apomorphine Injection in 5xFAD Transgenic Mice Are Partially Normalized in Those Chronically Pretreated with Apomorphine: The Time–Frequency Clustering of EEG Spectra - Vasily Vorobyov; Alexander Deev (Biomedicines)
Background: In experimental and clinical studies of pharmacological treatments for Alzheimer’s disease (AD), the electroencephalogram (EEG) frequency spectrum approach has demonstrated its efficacy in determining the characteristics of pathological changes in the functioning of different cerebral structures, interconnections between them, and disturbances in the brain neurotransmitter systems. The main results have been obtained in frames of traditionally used so-called “classical” EEG frequency bands: delta, theta, alpha, and beta. Objective: This unified approach simplifies comparing data from different studies but loses the dynamic peculiarities of the effects because of their time-dependent transition through the borders of the “classical” bands. Methods: In this study on non-narcotized freely moving 5xFAD transgenic mice, a model of AD, chronically pretreated with a non-selective dopamine (DA) receptor agonist, apomorphine (APO), we analyze the transitory EEG effects of acute APO injection in different brain areas by use of our “time–frequency” clustering program. The acute injection of APO was used to compare DA receptor sensitivity in 5xFAD mice pretreated with either APO or saline vs. wild-type (WT) mice pretreated with saline. Results: After acute APO injection, the clusters of enhanced EEG activity centered in the theta–alpha frequency range observed in WT mice disappeared in 5xFAD mice pretreated with saline and practically recovered in 5xFAD mice pretreated with APO. Conclusions: In 5xFAD mice pretreated with saline, the sensitivity of DA receptors was disturbed; chronic APO pretreatment mainly recovered this characteristic in 5xFAD mice. The “clustering” of pharmacological EEG effects and their time-dependent transition between classical frequency bands is a new effective approach for analyzing cerebral neurotransmission in neurodegenerative pathologies.